Tinjauan Sifat Fisik, Organoleptik, Kadar Protein Dan Kadar Kalsium Pada Variasi Pencampuran Getuk Kacang Tolo (Vigna Unguiculata) - Dwi Ratna Ningsih; Elza Ismail; Waluyo Waluyo (POLTEKKES KEMENKES YOGYAKARTA, 2017)
Getuk is traditional food that familiar in all age group. However, nutrient content of getuk not widely avaible. Cowpea containing protein and highcalcium have many beneficial for our body. This research aims to know the differences in physical characteristic, organoleptic and Phytic acid levels of getuk kacang tolo with mixing variations of cowpea. The kind of research is quasi experiment with simple random design using 4 treatment , 2 repiclates and 2 units of the experiment. The research sample is getuk kacang tolo with varians of cowpea 0% as control and getuk with the mixing variations of cowpea 25%, 50% and 75%. Physical characteristic were analyzed by descriptive. Organoleptic of data analysis using statistical tests Kruskal Wallis continued Mann-Whitney if there is a difference whereas Phytic acid levels using statistical test Anova continued Tukey if there is a difference. The results of this research is the addition of color produce more cowpea browned, the texture of mixing variations of cowpea not chewy whereas aroma and flavor are same with the control. The color of getuk kacang tolo with variations cowpea 50%, the texture of getuk kacang tolo with variations cowpea 75%, the aroma with variations cowpea 25% and the flavour getuk kacang tolo with variations cowpea 50% most preferred panelist. Protein levels in 100 g material with the variatins of cowpea 0%, 25%, 50% and 75% respectively are 1.16 g; 2.96 g; 4.56 g; 6.13 g. Calsium levels in 100 g material with the variations of cowpea 0%, 25%, 50% and 75% respectively are 237.2 mg; 388.1 mg; 596,27 mg; 736,57 mg. Conclusion of this research is the variations of mixing of cowpea in making getuk kacang tolo impact on physical characteristic, organoleptik, Protein levels and Calcium levels.